Gross output and livestock sales modelling in Spanish extensive farms using PLSR - Gaspar, Paula (107th EAAE Seminar "Modelling of Agricultural and Rural Development Policies". Sevilla, Spain, January 29 th -February 1st, 2008, 2008)
The aim of this paper is to model some production variables in extensive livestock farms located in the dehesa ecosystem. We intend to use not only purely economic variables in the construction of the model, but also structural variables in order to identify the characteristics of the farms that have the higher influence. Another objective is to be able to predict these variables at the farm level, using structural variables that are easy to measure. The data used in this work were obtained from a questionnaire survey to the holders/managers of a sample of 69 dehesa farms in Extremadura (SW Spain). The statistical methodology used for the construction of the model was Partial Least Square Regression (PLSR). It can be concluded that the variables relative to farm intensification, to labour and especially to Iberian pig breeding, are those that take part mainly in the model.
Keywords: Dehesa; gross output; Livestock farming systems; partial least square regression

Gross output and livestock sales modelling in Spanish extensive farms using PLSR - Gaspar, Paula (107th EAAE Seminar "Modelling of Agricultural and Rural Development Policies". Sevilla, Spain, January 29 th -February 1st, 2008, 2008)
The aim of this paper is to model some production variables in extensive livestock farms located in the dehesa ecosystem. We intend to use not only purely economic variables in the construction of the model, but also structural variables in order to identify the characteristics of the farms that have the higher influence. Another objective is to be able to predict these variables at the farm level, using structural variables that are easy to measure. The data used in this work were obtained from a questionnaire survey to the holders/managers of a sample of 69 dehesa farms in Extremadura (SW Spain). The statistical methodology used for the construction of the model was Partial Least Square Regression (PLSR). It can be concluded that the variables relative to farm intensification, to labour and especially to Iberian pig breeding, are those that take part mainly in the model.
The following values have no corresponding Zotero field: periodical: 107th EAAE Seminar "Modelling of Agricultural and Rural Development Policies". Sevilla, Spain, January 29 th -February 1st, 2008
Keywords: Dehesa; gross output; Livestock farming systems; partial least square regression